Analisis Kelayakan Rujukan Persalinan Oleh Bidan Puskesmas PONED Di RSUD Pirngadi Medan 2012 - Sari, Rumita Ena (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background : Referral feasibility by PONED midwives should be studied. Referral feasibility is deliver mother who indicated medical emergency by midwife. Referral feasibility should be suitable between PONED Health Centre and Hospital diagnostic. The aim of this study is to analyze referral feasibility by PONED midwives in Pirngadi Medan Hospital in 2012. Methode : This is a quantitative research using cross sectional design. Sample in this study are all referral cases referred to Pirngadi Hospital were 136 cases and supplemented by information from 17 midwives in 6 PONED Health Centre, and using an obgyn opinion. Data used a questionnaire, checklist, and medical record. Result : There were 106 cases referred to decent referral and 33 cases referral were not feasible referenced. Conclusion : There were 75,7% of the cases referred to decent referral by PONED midwives and 24,3% of cases referral is not feasible referenced Keywords : Referral feasibility, Maternal labor, Midwives, PONED Health Centre